Meeting the Needs of Vulnerable Primary Care Patients Without COVID-19 Infections During the Pandemic: Observations From a Community Health Worker Lens. (January 2022) - Carter, Jocelyn; Hassan, Susan; Walton, Anne
Background: During the height of the COVID-19 pandemic, healthcare systems were forced to focus their efforts on the rapidly rising numbers of patients contracting COVID-19. Although a myriad of publications focused on COVID-19 care have rapidly emerged, few have studied the impact of the pandemic on care received by patients without COVID-19. Objectives: To identify the experiences of Medicaid patients without COVID-19 related illness during the pandemic through the lens of community health worker outreach. Methods: From July 15, 2020 through February 1, 2021 patients previously enrolled in the C-CAT initiative were contacted by telephone for patient check-ins by CHW staff. Results: A total of 24 patients were contacted telephonically. Six patients had no active needs. Of the remaining patients, 70% of participants indicated that they had been unable to communicate with PCP or physician specialist care teams since the beginning of the pandemic and requested assistance from our CHW. Resulting unmet needs included the inability to obtain prescriptions drugs, necessary medical equipment, or supplies. Conclusion: The shift to COVID-19 focused care during the pandemic limited access to primary care for patients without COVID-19. The identified unmet patient needs included obtaining prescription medications, acute on chronic clinical condition management, healthcare services at home, and connection to social services. CHWs are uniquely positioned to assist patients as they connect to necessary clinical care, whether it be virtual or in-person, as they recover from the pandemic experience.